2021
DOI: 10.1111/jfbc.13869
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from purple sweet potato alleviate doxorubicin‐induced cardiotoxicity in vitro and in vivo

Abstract: In this study, anthocyanins were extracted and purified from purple sweet potato anthocyanins (PSPA) and the alleviative effect of PSPA on doxorubicin (DOX)‐induced cardiotoxicity was investigated. High Performance Liquid Chromatography‐Mass Spectrometry (HPLC‐MS) results showed that 10 kinds of substances were identified in PSPA and the PSPA was mainly composed of cyanidin (62.9%) and peonidin (21.46%). In in vitro experiments, PSPA reduced the excessive release of inflammatory factors (NO and TNF‐α) induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Anthocyanins are widely used in cosmetics and in food colorings in industry [60][61][62][63]. Numerous studies have shown that anthocyanins have very good medicinal value and significant health effects, such as anti-cancer, anti-inflammation, anti-aging, anti-obesity and protection of vision [64][65][66][67][68]. A a considerable supply of anthocyanins is required for industry use.…”
Section: Model Validation With An Independent Datasetmentioning
confidence: 99%
“…Anthocyanins are widely used in cosmetics and in food colorings in industry [60][61][62][63]. Numerous studies have shown that anthocyanins have very good medicinal value and significant health effects, such as anti-cancer, anti-inflammation, anti-aging, anti-obesity and protection of vision [64][65][66][67][68]. A a considerable supply of anthocyanins is required for industry use.…”
Section: Model Validation With An Independent Datasetmentioning
confidence: 99%
“…Anthocyanin from purple sweet potato had decreased doxorubicin cardiac toxicity using different concentrations (100, 200, and 400 μg/mL) according to in vitro and in vivo study. The previously mentioned effect was due to the decrease in inflammatory factors, such as nitric oxide and TNF-α, also due to the decline in creatine kinase, trimethylamine oxide, and lactic dehydrogenase triggered by myocardial damage [ 293 ]. Moreover, with 20 μg/mL trastuzumab, 1 μg/mL anthocyanins cyanidin 3 glucoside proved to show a synergistic effect in vitro and in vivo.…”
Section: Combination Therapies Based On Selected Natural Productsmentioning
confidence: 99%
“…The high acylated anthocyanin content provides color and greater stability and is directly absorbed into the bloodstream [ 5 , 6 ]. Previous studies have suggested that PSPA shows a plethora of biological activities, including antioxidant [ 7 ], anti-inflammatory [ 8 ] anticancer [ 9 ], and cardiovascular protective functions [ 10 ]. Many of these health benefits are attributed to the potent antioxidant activity of anthocyanins, which can protect DNA, proteins, and lipids from damage and activate specific detoxification enzymes, such as glutathione reductase, glutathione peroxidase, and glutathione S-transferase, to reduce oxidative stress [ 11 ].…”
Section: Introductionmentioning
confidence: 99%